Effects of an ergothioneine-rich Pleurotus sp. on skin moisturizing functions and facial conditions: a randomized, double-blind, placebo-controlled trial - Hanayama, Motoki; Mori, Koichiro; Ishimoto, Takahiro; Kato, Yukio; Kawai, Junya (Frontiers in Medicine, 2024)
Background: L-ergothioneine (EGT), an antioxidative and anti-inflammatory amino acid, is abundant in various mushroom fruiting bodies. Meanwhile, the effects of EGT-containing mushrooms on human skin are unknown. This study investigated the effects of oral ingestion of a novel EGT-rich strain of Pleurotus species (hiratake) on skin conditions in humans.We conducted a 12-week, randomized, double-blind, placebo-controlled, parallel-group trial to evaluate skin moisturizing functions and facial conditions in 80 healthy women who were randomly assigned to either a group that was supplemented with hiratake tablets containing 25 mg of EGT/day or a placebo group. Skin moisture content, transepidermal water loss (TEWL), and facial scores (VISIA scores) were measured at baseline, 8 weeks, and 12 weeks of supplementation.Results: At 8 weeks, the skin moisture content was significantly higher on the temple in the hiratake group than in the placebo group. The hiratake group also exhibited a significant increase in skin moisture content on the arm at 8 and 12 weeks compared with baseline. At 12 weeks, wrinkle and texture scores were significantly better in the hiratake group than in the placebo group, and plasma EGT concentrations in the hiratake group were 4.7-fold higher than baseline (from 3.4 to 15.9 µM). Furthermore, EGT concentrations in plasma were significantly correlated with improvements in skin moisture content and TEWL on the arm, implying that these skin moisturizing benefits could be partly attributed to EGT. A stratified analysis of participants with a low baseline plasma EGT concentration (< 3.3 µM) revealed that skin moisture content on the temple was significantly higher at 8 and 12 weeks, and skin moisture content on the arm at 12 weeks tended to be higher (p = 0.074), in the hiratake group than in the placebo group. These findings suggested that oral ingestion of EGTrich hiratake can improve skin moisturizing functions.EGT-rich hiratake may help maintain skin conditions in healthy women, and EGT may play a role in these beneficial effects.